2021
DOI: 10.3390/cancers13133285
|View full text |Cite
|
Sign up to set email alerts
|

Control of Skeletal Muscle Atrophy Associated to Cancer or Corticosteroids by Ceramide Kinase

Abstract: Apart from cytokines and chemokines, sphingolipid mediators, particularly sphingosine-1-phosphate (S1P) and ceramide 1-phosphate (C1P), contribute to cancer and inflammation. Cancer, as well as other inflammatory conditions, are associated with skeletal muscle (SkM) atrophy, which is characterized by the unbalance between protein synthesis and degradation. Although the signaling pathways involved in SkM mass wasting are multiple, the regulatory role of simple sphingolipids is limited. Here, we report the impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Of interest, other molecular processes have been similarly involved in these phenotypes, including the C1P-mediated vascular endothelial growth factor (VEGF) production in macrophages [22] or C1P-induced lysophosphatidic acid (LPA) receptor activation in myoblasts [23]. In line with the latter report, Meacci and co-workers have recently shown that the CERK/C1P axis plays a crucial role as molecular regulator of skeletal muscle mass associated with cancer [24]. In addition to stimulating cell proliferation, C1P can increase cell number through the inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 77%
“…Of interest, other molecular processes have been similarly involved in these phenotypes, including the C1P-mediated vascular endothelial growth factor (VEGF) production in macrophages [22] or C1P-induced lysophosphatidic acid (LPA) receptor activation in myoblasts [23]. In line with the latter report, Meacci and co-workers have recently shown that the CERK/C1P axis plays a crucial role as molecular regulator of skeletal muscle mass associated with cancer [24]. In addition to stimulating cell proliferation, C1P can increase cell number through the inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 77%
“…The activation of protein degradation-related pathways is the cause of muscle atrophy in cachexia. Skeletal muscle degradation is usually accompanied by the activation of the ubiquitin system, upregulation of MAFbx, and downregulation of MyHC expression in muscle-specific E-3 ubiquitin ligase [ 16 ]. The expression of active caspase3 in mice was upregulated after cisplatin, indicating the occurrence of muscle apoptosis, which could be improved by SLI treatment ( Figure 4(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…MAPK pathway additionally inhibits the proliferation and differentiation of myocytes. CCAAT/enhancer-binding proteins-6 beta (C/EBPb) is a major regulator of myoblast and is activated by IL-6 and IL-1, resulting in myogenesis inhibition and muscle fiber size reduction [ 8 , 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…GDF-15 is another cytokine belonging to the TGF-beta family which is increased in cancer cachexia and is responsible for the regulation of lean body mass and body weight [ 15 ]. TNF-α also decreases the ceramide kinase reducing the conversion of ceramide to ceramide-1-phosphate leading to ceramide accumulation and resulting in myotube atrophy [ 26 ]. In addition to these effects, IL-6 brings about changes in redox balance in muscle tissue by inhibiting the anti-oxidant work and increasing the fast fibers in muscle which are more prone to atrophy [ 27 ].…”
Section: Reviewmentioning
confidence: 99%